2020
DOI: 10.1371/journal.pone.0228863
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ineffective breastfeeding technique and associated factors among lactating mothers attending public health facilities of South Ari district, Southern Ethiopia

Abstract: IntroductionImproper positioning, attachment, and suckling are constructs for ineffective breastfeeding technique (IBT). IBT results in inadequate intake of breast milk, which leads to poor weight gain, stunting, and declines immunity. Besides, IBT increases the risk of postpartum breast problems. Despite its impact on maternal and child health, breastfeeding technique is not well studied in Ethiopia. Hence, the purpose of this study was to assess the prevalence of IBT and associated factors among lactating mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
56
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 18 publications
10
56
3
1
Order By: Relevance
“…This shows the use of BFT is poor in women giving birth for the rst time. This is in line with the nding from studies in India, Australia, and Ethiopia (3,37,38,48). This could be due to a reason multiparous mothers might have frequent BFT counseling and exposure previously, which may enable them to acquire and master the skill of breastfeeding, unlike primipara.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This shows the use of BFT is poor in women giving birth for the rst time. This is in line with the nding from studies in India, Australia, and Ethiopia (3,37,38,48). This could be due to a reason multiparous mothers might have frequent BFT counseling and exposure previously, which may enable them to acquire and master the skill of breastfeeding, unlike primipara.…”
Section: Discussionsupporting
confidence: 85%
“…This nding remarks that ANC follow-up has added postpartum purposes beyond assessing pregnancy risks and giving appropriate care. Similar ndings were reported from a study done in Karnataka India, Libya, Harar city, and Ari southern Ethiopia (13,14,36,48). Antenatal counseling may enhance the mother's knowledge and help them to convert this knowledge to practice as early as possible after delivery, whether they get immediate post-natal counseling or not.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…They modi ed the baby's position to allow good attachment to resolve cracked nipples. Yilak et al (2020) reported that poor positioning was more likely to exhibit ineffective breastfeeding techniques, potentially causing nipple pain [24]. As the mothers had cracked nipples due to ineffective suckle lead to having insu cient milk supply.…”
Section: Discussionmentioning
confidence: 99%